Entre normalizações e estranhamentos: tensões subjetivas nos processos de tornar-se mãe - Azevedo, Maria Renata Florêncio de (2022)
In our historical reality, we identified that there is an ideal model of motherhood rooted in sexist discourses, which works as a device of power when we analyze that, the conditions of emergence of this model of motherhood and the injunctions that stem from it in the process of maternal subjectivation, it is less a concern for the well-being of children, and more of a political project. At the same time, we have that this historical reality - which gave emergency conditions for this device - has been undergoing significant changes in its assumptions, so that maternal subjectivation is no longer the only form of personal fulfillment for women, in other words, is no longer the only way for women to become people. However, the experience of possible motherhood, subordinates’ women to a subjective performance - pre-established relationships about what should be thought, said, seen and practiced, centralizing subject positions on them, which tries to address them to an overload of work and a progressive subjective and social erasure. Based on this understanding, we propose the thesis that, in the process of maternal subjectivation, the lines of subjectivity move between the estrangement and the normalization of sexist discourses, which address women to repositionings that socially weaken the way they experience themselves. and reinforce gender inequalities. Thus, the present study has the general objective: To analyze the subjective productions in movement in the experience of motherhood, from subject positions, actions and discursive effects in the process of becoming a mother, and how these have reverberated in the treatment of the self. This was an exploratory, cross-sectional study with a qualitative design, which allowed the analysis of subjective productions in motion in the experience of motherhood and the vicissitudes encountered by these mothers in this context. The surveys were carried out in the places proposed by the participants, considering the physiological and emotional condition of women-mothers and their children, mainly due to the limitations imposed by the social isolation experienced during the Covid-19 pandemic. This is a convenience sample (non-probabilistic), composed of 9 primiparous mothers with children between 1 year and 2 years old, married, aged between 24 and 35 years. A sociodemographic questionnaire was used and a semi-structured interview was carried out. The analysis of the data collected in the interviews was carried out from the Discourse Analysis, inspired by the Foucauldian contributions, outlining the relations produced from the normative practices and their discursive effects, we observed that the lines of subjectivation that work as a guide to action and subjectivity-forming fragments, move between the normalization of discourses with positions legitimized by sexist discourses, being able to address frameworks of understanding of reality based on the reproduction of these historical roots that only contribute to the perpetuation of relations of inequality, exploitation and oppression, and the estrangement of these discourses with insurgent positions, being able to address to frameworks of understanding of reality that maximizes the possibilities of conducting oneself in relationships with oneself in the experience of motherhood. I can conclude from this that the power relations that women establish with the lines of subjectivation of the maternal device, when analyzed with a view to understanding their tensions - between normalization and estrangement - with their respective effects, considering the historical constitution that made them emerge, it will be possible to build maternal conjugations that do not end in individual conflicts and ambivalences, that is, it will be possible to think of other forms of relationship with truths, other ways of being and acting that are not always reiterated by hegemonic truths, which produce a stylization mass of subjectivities.